2001
DOI: 10.1086/501843
|View full text |Cite
|
Sign up to set email alerts
|

Presence and Chromosomal Subtyping of Legionella Species in Potable Water Systems in 20 Hospitals of Catalonia, Spain

Abstract: Legionella was present in the water of most of the hospitals studied; each such hospital had a unique, dominant chromosomal DNA subtype. The verification of several genomic DNA restriction profiles in such a small geographic area demonstrates the great genetic diversity of Legionella in the aquatic environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
32
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 31 publications
2
32
0
Order By: Relevance
“…A recent publication on the findings of a study carried out in 20 hospitals 4 showed that over 80% of their water supplies were contaminated with Legionella spp.…”
Section: Introductionmentioning
confidence: 99%
“…A recent publication on the findings of a study carried out in 20 hospitals 4 showed that over 80% of their water supplies were contaminated with Legionella spp.…”
Section: Introductionmentioning
confidence: 99%
“…Genetic diversity was also suggested using different typing methods (Selander et al 1985;Sabria et al 2001;Aurell et al 2003;Amemura-Maekawa et al 2005), but attempts to correlate sequence types (ST) and epidemiological characteristics of strains were unsuccessful (Aurell et al 2005). However, among L. pneumophila strains that cause human infections, significantly less diversity was found than among environmental isolates (Harrison et al 2007) and a correlation between specific clones and the ecological niche was shown (Amemura-Maekawa et al 2005).…”
mentioning
confidence: 99%
“…All isolates were analyzed by PFGE as described previously (10). According to the criteria of Tenover et al (13), chromosomal PFGE patterns differing in one or more bands were considered distinct in this study.…”
mentioning
confidence: 99%